Queer as Africa: Representations of queer lives in selected Nigerian, Kenyan, and South African literature and film - Wilson, Jon Stephen Edward (Rhodes University, Faculty of Humanities, Department of Literary Studies in English)
This thesis contests the notion that nonnormative sexualities are 'un-African' by examining a range of representations of queer African lives on film and in literature, produced by Africans for Africans, as a means to interrogate the role played by the interconnected histories of colonialism, religion, and the policing of queer intimacy, specifically in Kenya, Nigeria, and South Africa. Through a close reading of a selection of texts from these three countries, this thesis takes a cultural-historical approach to exploring the complex struggles engaged in by queer people in Africa to protections under the law, and to represent themselves in literary and cinematic narratives. The first chapter is focused on the Kenyan film Rafiki (2018), directed by Wanuri Kahiu, which tells the story of queer love between two young Kenyan women who face the vehement condemnation of their relationship from their homophobic community. The film was banned in Kenya, but the director was granted a temporary injunction by Kenya's high court in order for it to be screened in Nairobi. This made Rafiki the first queer film ever to be screened in Kenya, and viable for an Academy Award nomination. The second chapter focuses on the bold assertion of a queer African identity through the short story collections Queer Africa: New and Collected Fiction (2013) and Queer Africa 2: New Stories (2017). Written by various authors from the African continent, and compiled and edited by Karen Martin and Makhosazana Xaba, both collections offer a wide variety of fictional narratives focused on queer experiences in Africa. The second chapter has a focus on stories from Kenyan and Nigerian authors and explores notions of home, queer belonging, and visibility. The third chapter presents a close reading of the South African film Inxeba (2017), also known as The Wound, directed by John Trengove and adapted by Trengove and Thando Mgqolozana from Mgqolozana's novel, A Man Who Is Not A Man (2009). The film depicts the traditional Xhosa initiation ritual, ulwaluko, and is set in the rural Eastern Cape. Inxeba is an important case study in the history of queer representation in Africa, as the film hit a nerve with many, interrogating what South Africans believe about culture, traditions, masculinity, and the right of artists to represent sacred ritual in art. This thesis pays attention to the historical entanglements between homophobia, imperialism, and Christianity "“ relationships that continue to affect the experiences of queer people in Africa and attitudes towards them and interrogates why queer individuals are still being left out of efforts towards creating a new normal in postcolonial Africa. This thesis suggests that increased visibility is a key aspect of queer activism in Africa "“ through the act of representation, sharing lived experiences, and telling queer stories.
Keywords: Africans in literature; Africans in motion pictures; Homosexuality in literature; Homosexuality in motion pictures; Sexual minorities in literature; Sexual minorities in motion pictures; African literature History and criticism; Motion pictures, African History and criticism; Sexual minorities -- South Africa Public opinion; Sexual minorities Kenya Public opinion; Sexual minorities Nigeria Public opinion; Sexual minorities -- South Africa Social conditions; Sexual minorities Kenya Social conditions; Sexual minorities Nigeria Social conditions